2019
DOI: 10.1111/1471-3802.12481
|View full text |Cite
|
Sign up to set email alerts
|

Teachers and differentiated instruction: exploring differentiation practices to address student diversity

Abstract: Given the increasing diversity of the student body, teachers are called to appropriately address students' various learning needs by means of differentiated instruction (DI). However, empirical research has yielded mixed evidence on teachers' reported use of DI. Using nationally representative data from the National Educational Panel Study in Germany, this article aimed to explore German (as native language) and Mathematics teachers' use of DI practices. In addition, this study took into consideration contextu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 53 publications
4
61
1
8
Order By: Relevance
“…( 2020 ) wurde die Taxonomie der Binnendifferenzierung nach Pozas et al. ( 2020 ) eingesetzt. In diesen wenigen Studien ist es daher möglich im Rahmen der Datenauswertung für den Messfehler zu kontrollieren.…”
Section: Review 1: Beschreibung Der Befragungen Entlang Des Forschungunclassified
“…( 2020 ) wurde die Taxonomie der Binnendifferenzierung nach Pozas et al. ( 2020 ) eingesetzt. In diesen wenigen Studien ist es daher möglich im Rahmen der Datenauswertung für den Messfehler zu kontrollieren.…”
Section: Review 1: Beschreibung Der Befragungen Entlang Des Forschungunclassified
“…Jafari Kuzu ve diğerleri (2018) de Türkiye'deki çalışmalarında, kimi öğretmenlerin öğrenci merkezli çalışmalara derslerde yer verdiklerini, bir kısım öğretmenin ise bu konuda çalışma yapmadığını bildirmiştir. Çok sayıdaki çalışmada, ortalamaya göre yapılan eğitimin yararlı olmadığı, öğretimin farklılaştırılmasının öğrencilerin akademik başarısını, tutumunu ve motivasyonunu olumlu etkilediği belirtilmektedir (Rose, 2017;Pham, 2012;Pozas, Letzel ve Schneider, 2019). Amerika'da yapılan bir çalışma ise farklılaştırılmış öğretimi benimseyen öğretmenlerin mesleki yeterlik inancı bakımından meslektaşlarından pozitif yönde farklılaştıklarını bildirmektedir (Dixon, Yssel, McConnell ve Hardin, 2014).…”
Section: Discussionunclassified
“…Teachers’ use of differentiated instruction has also been addressed in the literature with studies focusing on how often teachers use differentiated instruction (e.g., Archambault et al, 1993; Moon et al, 1995; Pozas et al, 2020; Suprayogi et al, 2017), factors affecting such use (e.g., King, 2010; Suprayogi et al, 2017), and their perceptions of differentiated instruction (King, 2010; Santangelo & Tomlinson, 2012). Archambault et al (1993) and Moon et al (1995) are the most recent publications reporting on how often teachers in the United States differentiate instruction with nationally representative samples.…”
Section: Differentiated Instruction: Empirical Supportmentioning
confidence: 99%
“…Archambault et al (1993) and Moon et al (1995) are the most recent publications reporting on how often teachers in the United States differentiate instruction with nationally representative samples. Pozas et al (2020) conducted a national survey of teachers in Germany and found that tiered assignments and ability grouping were among differentiation strategies most frequently used. Suprayogi et al (2017) found that teachers in Indonesia implement differentiation to a great extent ( M = 7.31 on a 10-point scale) and that teachers’ self-efficacy beliefs with regard to differentiation and constructivist teaching beliefs as well as classroom size were associated with teachers’ use of differentiation.…”
Section: Differentiated Instruction: Empirical Supportmentioning
confidence: 99%